Developing Prosocial Leadership in Primary School Students: Service-Learning and Older Adults in Physical Education - Encarnación E. Ruiz-Montero; Horacio Sanchez-Trigo; Kamal Mohamed-Mohamed; Pedro Jesús Ruiz-Montero (Education Sciences)
Background: As population aging continues to accelerate, it is increasingly important to promote a positive perception of older adulthood from an early age. Service-Learning (SL), when integrated into Physical Education (PE), offers an opportunity to foster critical and prosocial awareness in primary school students, encouraging attitudes of respect and empathy toward older adults. Method: A qualitative study was conducted with 40 sixth-grade students who participated in an SL project at an adult day care center. Through weekly adapted PE sessions, the students engaged in direct interaction with older adults. Data were collected through reflective journals and analyzed using content analysis techniques. Results: The findings reveal a positive impact on students’ perceptions of older adults. Significant development of prosocial competencies, such as empathy, collaborative leadership, and communication skills, was observed. Furthermore, students expressed an enhanced sense of usefulness and social commitment. Conclusions: Intergenerational SL in PE is an effective strategy for improving academic learning, transforming attitudes, promoting civic values, and contributing to more inclusive education.